Women through the development gaze of the World Bank: legal reforms and the myth of empowerment in the Global South - Salem, Mariam (AUC Knowledge Fountain, 2020)
Historically, women were largely invisible to early development planners and they were only discussed in passive terms. This was based on the assumptions about the gendered division of labor and women's supposed absence from the productive labor. However, development discourses today are full of images of the empowered women in the Global South; she is the selfless mother, the strong entrepreneur and the resourceful breadwinner. The World Bank in particular depicts women in the Global South as vulnerable, marginalized, yet a major "untapped resource". The key is to acquire them with appropriate means along with the necessary legal reforms that would empower them against the traditional barriers and enable them access to the labor market. This depicts the gender equality as smart economics, which represents the primary modes by which women in the Global South became visible through the development gaze of the World Bank. The idea here is to show how the World Bank has redefined feminism to resonate with its neoliberal agenda. In order to understand how these legal reforms legitimize the work of the World Bank's private partners and the underlying reasons behind framing women in the Global South to become visible in those specific characteristics, it is helpful to analyze World Bank Gender and Development reports, starting from 2012 to 2018. This paper argues that this specific feminism that is promoted by the World Bank has its costs and those legal reforms maximize the profits of their private partners. It has left those women suffering from a new kind of violence caused by the neoliberal agenda in addition to their already existing oppression from their unpaid work. This analysis will demonstrate the World Bank’s construction of women in the Global South and the true cost of those legal reforms on their lives.